Pelatihan Buket Bunga dari Sampah Plastik pada Santri Pondok Pesantren Yawapi Asy-Sya’ban - Diana Zalfanur; Intan Nadzifa; Lestari, Istikomah Dwi; Ade Gunawan; Hendri Hermawan Adinugraha (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
One form of waste is plastic waste which continues to increase every year in various parts of the world in line with the increasing need for people to use plastic. Plastic waste, which has been thrown away after being used and eventually causing environmental pollution, should be processed into a variety of attractive handicrafts that have high commercial value and benefits. The goal to be achieved from this service activity in general is so that students can creatively make flower bouquets independently in an effort to welcome National Teacher's Day so that they can give their work to their teachers. The method used in this community service activity is three methods, namely empowerment, training and mentoring. These three methods are put together in a dedication because in their implementation they can become an arrangement that is in accordance with the goals to be achieved. From the community service activities that have been carried out, it was found that from the process of delivering the material, 90% of the participants really understood the material presented and from the 10 female students who were divided into 5 groups, there were 4 groups or 8 children who were able to make flower bouquets creatively.